Pengembangan Media Kartu Truth or Dare Untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran PPKn Kelas VI Materi Pancasila - Amelya, Ryah; Arini, Novanita Whindy (Universitas Negeri Padang, 2024)
The enthusiasm of high-grade students at SDN Batu Ampar 08 Pagi towards the values of Pancasila in attitude and action still needs to be higher. This is due to the lack of learning that emphasizes character deepening, so students are very minimal in applying these values in attitude. With this, researchers developed learning media in the form of Truth or Dare cards, which are expected to help improve students' understanding of Pancasila values. This research uses the Research and Development (R&D) method using the ADDIE development model and uses quantitative and qualitative approaches. The validation showed satisfactory results with a validation score of 96% by material experts, 94.3% by media experts, and 93.3% by education experts, resulting in an average validation percentage of 91.3%, which is feasible. In this study, testing was carried out in two stages: a small trial with a score of 91.6% and a large trial with a score of 91.9%, with very feasible qualifications. If the two trial results are combined, an average score of 84.1% is obtained, indicating that this media is feasible to use. The effectiveness of Truth or Dare card media in improving students' understanding of Pancasila values was measured using pre-test and post-test. The pre-test score of 43.7% increased to 61.11% in the post-test, showing an increase of 17.41%. The field test analysis showed an N-gain (g) value of 0.81, which is included in the high classification, indicating that the Truth or Dare card media has a high potential effect. Thus, the Truth or Dare card media is declared feasible and effective in improving the understanding of Pancasila values in high-grade students.